The relationship between various jump tests and baseball pitching performance: A brief review - Lis, R.; Szymanski, D. J.; Crotin, R. L.; Qiao, M. (Strength and Conditioning Journal, 2024)
Multidirectional ground reaction forces (GRFs) and jump tests within baseball pitchers provide insight into athletic ability and coordination to produce lower-body force and power. Lower-body power is a biomechanical feature that denotes physiological capacity through dynamic and passive tissue stretch-shortening in transferring energy from the ground through the kinetic chain. Optimized lower-body power may lessen the magnitude of forces on the upper extremity. Insufficient lower-body power may create a greater risk of upper-body injury. Lower-body power and its relationship to ball velocity have been minimally investigated, yet some research points to a correlation between jumping ability and fastball velocity. Because pitching is unilateral, practitioners should consider unilateral jumps to determine the extent of bilateral asymmetry or stride to drive leg differences that can guide training to remediate deficiencies. The purposes of this brief review are to (a) examine factors that influence vertical jump performance among baseball players, (b) examine research on pitching multidirectional GRFs, and (c) examine literature concerning jump performances to baseball pitching performance. Collectively, this review can assist coaches and practitioners in lower-body power testing and training for baseball pitchers.